1999
DOI: 10.1038/sj.ejhg.5200334
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of genomic structures and expression patterns of two closely related flanking genes in a critical lung cancer region at 3p21.3

Abstract: In the search for a tumour suppressor gene in the 3p21.3 region we isolated two genes, RBM5 and RBM6. Gene RBM5 maps to the region which is homozygously deleted in the small cell lung cancer cell line GLC20; RBM6 crosses the telomeric breakpoint of this deletion. Sequence comparison revealed that at the amino acid level both genes show 30% identity. They contain two zinc finger motifs, a bipartite nuclear signal and two RNA binding motifs, suggesting that the proteins for which RBM5 and RBM6 are coding have a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 13 publications
1
69
0
Order By: Relevance
“…This finding, although it needs to be validated by actual experiments, such as a gel-shift assay, is in a good correlation with the previous observations that the H37 protein contains RNA-binding motifs (i.e., RBM5 is another name for H37/Luca15; refs. 15,32), and H37 shows in vitro RNA-binding activity (33). Taken together, our current hypothesis is that H37 may function in some aspects of post-transcriptional regulations of certain important proteins involved in cell cycle and/or apoptosis (i.e., Bax, cyclin A, RB, etc.).…”
Section: Discussionmentioning
confidence: 74%
“…This finding, although it needs to be validated by actual experiments, such as a gel-shift assay, is in a good correlation with the previous observations that the H37 protein contains RNA-binding motifs (i.e., RBM5 is another name for H37/Luca15; refs. 15,32), and H37 shows in vitro RNA-binding activity (33). Taken together, our current hypothesis is that H37 may function in some aspects of post-transcriptional regulations of certain important proteins involved in cell cycle and/or apoptosis (i.e., Bax, cyclin A, RB, etc.).…”
Section: Discussionmentioning
confidence: 74%
“…Loss of heterozygosity (LOH) occurs at 3p21.3 in 100% of small cell lung carcinoma (SCLC) cell lines, 490% of non-SCLC cell lines, and 490% of primary lung cancers (Gazdar et al, 1994), implying the existence of a lung cancer tumour suppressor gene in this region. Precise delineation of the deletions resulting in the LOH has been the focus of extensive study over the past 10 years (Daly et al, 1993;Imreh et al, 1997;Kashuba et al, 1995;Kholodnyuk et al, 1997;Kok et al, 1994;Sekido et al, 1998;Szeles et al, 1997;Todd et al, 1996;Wei et al, 1996;Yamakawa et al, 1993), and evidence exists that LUCA-15 is included in a number, but not all, of these lesions Szeles et al, 1997;Timmer et al, 1999;. However, as cancers which involve the short arm of chromosome 3 progress, the number/extent of lesions appears to increase, complicating analysis of important tumour suppressor regions (Chung et al, 1995;Kok et al, 1997).…”
mentioning
confidence: 99%
“…The RBM6 gene (1123 aa, NM_005777) spans the distal breakpoint of the NCI-H740 deletion , occupies more than 60 kb of genomic DNA, and encodes more than 16 exons expressed as a 4 kb mRNA in several human normal and lung cancer cell lines. Alternatively spliced forms have been described (Gure et al, 1998;Timmer et al, 1999). No mutations were found in 39 lung cancer cell lines.…”
Section: Rbm5 and Rbm6mentioning
confidence: 99%
“…No mutations were found in 39 lung cancer cell lines. Timmer et al (1999) using SSCP analysis of 16 lung cancer cell lines found a single presumably neutral mutation only in RBM5. However, by RT -PCR in the same study it was demonstrated the existence of two alternative splice variants of RBM6, one including and one excluding exon 5, in both normal lung tissue and lung cancer cell lines.…”
Section: Rbm5 and Rbm6mentioning
confidence: 99%